2020
DOI: 10.1163/25902539-00201008
|View full text |Cite
|
Sign up to set email alerts
|

Using Photovoice as Methodology, Pedagogy and Assessment Tool in Education: Graduate Students’ Experiences and Reflections

Abstract: Participatory visual methods are increasingly used in various disciplines. This article focuses on using photovoice as a methodology, pedagogy and participatory assessment tool in education through Chinese graduate students’ experiences with a photovoice project. The study investigated the efficacy of photovoice as a pedagogical and assessment tool, and the utility of photovoice as a participatory visual research method to examine impacts of globalization on China. A group of sixty Chinese students who studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…In particular, people with low literacy skills are likely to benefit, and it is even easier to attract children and adolescents who are more likely to choose pictures over text. However, the promise of a photovoice as a robust visual research methodology and pedagogy lies in the rigor, trustworthiness, and adaptation of the project design and process [43].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, people with low literacy skills are likely to benefit, and it is even easier to attract children and adolescents who are more likely to choose pictures over text. However, the promise of a photovoice as a robust visual research methodology and pedagogy lies in the rigor, trustworthiness, and adaptation of the project design and process [43].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported on college student participation in photovoice research projects to explore various social issues [ 2 , 4 ]. A few studies have documented the experiences and reflections of graduate students as facilitators of photovoice research [ 6 , 30 ]. To our knowledge, no study has yet reported on the reflections of college students who facilitated a photovoice research project.…”
Section: Introductionmentioning
confidence: 99%
“…There is overwhelming evidence to support the empowering potential of photovoice, a process whereby research participants take photographs to present their views on a significant aspect of their lives. First introduced in 1994 as Photo Novella by Wang and Burris (1997), photovoice has since proved to be a powerful research strategy that continues to be used across the social sciences, including in health, health promotion and health education (Liebenberg, 2018; Wang, 2020). The work of Wang and Burris suggests photovoice methodology is political in that it derives from critical theory, which centralises issues of power and social justice.…”
Section: Introductionmentioning
confidence: 99%
“…First, unlike other photographic research approaches, photovoice typically uses participant-generated pictures and an analytical interview protocol to prompt discussions that seek to promote self-awareness, advocacy and the emergence of novel ideas (Cooper and Yarbrough, 2010; Esau et al, 2016; Henry et al, 2013). Second, photovoice aligns with collaborative analysis, even though photovoice researchers tend to use conventional qualitative approaches to data analysis (Wang, 2020). Third, photovoice demands close attention to ethics, especially concerning the taking of photos and dissemination of research findings (Creighton et al, 2018).…”
Section: Introductionmentioning
confidence: 99%